Clinical observation of phacoemulsification combined with goniosynechialysis for treatment of angle-closure glaucoma - Qi Zhang (Guoji Yanke Zazhi, 2013)
AIM: To investigate the clinical effects of phacoemulsification combined with goniosynechialysis for treatment of angle-closure glaucoma. METHODS: A total of 86 patients(96 eyes)with angle-closure glaucoma and cataract were enrolled in the study and they were divided into two groups. Group A included patients with anterior goniosynechia closure of 18°-270°(270° included), and group B included patients with anterior goniosynechia closure greater than 270°.The therapeutic effects were observed. RESULTS: Operation was successful in all patients and there was no intraoperative posterior capsule rupture. During the 6-month follow-up, the intraocular pressure and drug use of group A were both less than those of group B(P<0.05); the anterior chamber depth, the distance vision and goniosynechia closure range in Group A were better than those in Group B(P<0.05). Corneal edema was the main complication in both groups(5 cases,5.8% in each group)and all patients were cured after symptoms were properly controlled. CONCLUSION: Phacoemulsification combined with goniosynechialysis was effective for patients with anterior goniosynechia closure of 18°-270°(270° included).